(3eSJbHd GdShOGf ai Xd GJaGb GdSdGe GdTGed (B2005 (3e (B/ s - (3eMeO UGdM YeQ Ydi CHheWGQis; (3EHQGgje fUQGdOjf (B: s; (3UHMi bfUhg (B: s ((3GdbGgQI (B: s (3eMeO UGdM YeQ Ydi CHheWGQi (B: s, 2013)
(3jYO GdShOGf fehPLB eUZQB dEaQjbjG GdJi JYGfi ef GdYOjO ef GdETcGdGJ PGJ GdWHjYI GdNGUI (B: (3ShAB (B((3ShGA(B) (3ef MjK JYOO GdKbGaGJ h GdGfJeGAGJ GdbHdjI h GdOjfjI Ch ef MjK eYGfGJgG ef GdSjWQI GdGSJYeGQjI GdJi eGQSJ ajgG SjGSGJ dJcQjS GdaQbI h GdNdGa (B: (3GHJOCJ HJbSje GdbGQI habB ddMOhO GdMGdjI GdJj cGfJ SHHB CSGSjB aj CZdH MGdGJ GdUQGY OGNd GdbGQI (B: (3aVdB Yf Ndb Ch JMQjc YhGed GdGfbSGe OGNd GdOhdI GdhGMOIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3eYgO GdHMhK h GdOQGSGJ GdCaQjbjI (B- (3bSe GdfXe GdSjGSjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GJaGb GdSdGe GdTGeds; (3GdMQcI GdTYHjI dJMQjQ GdShOGf s; (3GdShOGf s